Determinants of customer loyalty in cellular service sector of Pakistan: mediating and moderating effects - Tariq, Beenish (2018)
The customer loyalty has become essential for survival and success of cellular service providers with the saturation and maturity of the cellular service sector of Pakistan. This research focuses on the direct and indirect determinants of customer loyalty of the prepaid segment in the cellular service sector of Pakistan. This study examines the direct influence of perceived service quality, perceived value, sales promotion, perceived corporate social responsibility, customer satisfaction, and customer trust on customer loyalty. This research also examines the role of customer satisfaction and customer trust as a mediator and government regulations as a moderator towards customer loyalty. The consideration of putting both mediators and moderator in this research allows a more precise description of the relationship between all the variables mentioned and the outcome of the research. The model under study is developed using the proven predictive power of the Oliver's Four Stage Loyalty Model and The Nudge theory. A total of 392 prepaid cellular service consumers located in capital cities of four provinces of Pakistan participated in this study through mall-intercept sampling technique. The PLS SEM analysis results indicated that perceived service quality, customer satisfaction and customer trust are significant positive direct determinants of customer loyalty. In addition, perceived service quality, sales promotion, perceived corporate social responsibility are significant positive determinants of customer satisfaction. Moreover, perceived service quality, perceived corporate social responsibility and customer satisfaction are significant positive determinants of customer trust. Furthermore, perceived service quality and corporate social responsibility revealed as significant positive indirect determinants of customer loyalty through the mediation of customer satisfaction and customer trust. Finally, the findings indicate the significant positive moderation of government regulations for the relationship between perceived value and customer loyalty and significant and negative moderation for the relationship between perceived corporate social responsibility and customer loyalty. This study also provided some valuable insights on how customer loyalty can be captured in the cellular service sector of Pakistan, where government regulations are influencing the behaviour of cellular consumers. It also suggested the government as a policymaker to understand the effectiveness of its regulations in the cellular service sector of Pakistan. Furthermore, this study is limited to prepaid cellular sector of Pakistan and suggested to incorporate the other segments of cellular sector in future studies.